Broadband : should we regulate high-speed internet access? - Crandall, Robert W.; Alleman, James H. (AEI-Brookings Joint Center for Regulatory Studies, 2002)
A Brookings Institution Press and American Enterprise Institute publication There is widespread concern in the telecommunications industry that public policy may be impeding the continued development of the Internet into a high-speed communications network. In the absence of ubiquitous, high-speed ¡°broadband¡± Internet connections for residential and small-business customers, the demand for IT equipment and new Internet service applications may stagnate. Broadband policy is controversial in large part because of the differences in the regulatory regimes faced by different types of carriers. C.